Proposal for selective isotope transmutation of long-lived fission products using quasi-monochromatic γ-ray beams. Issue 12 (1st December 2016) - Hayakawa, Takehito; Miyamoto, Shuji; Hajima, Ryoichi; Shizuma, Toshiyuki; Amano, Sho; Hashimoto, Satoshi; Misawa, Tsuyoshi
ABSTRACT: We have proposed a new selective isotope transmutation method using photonuclear reactions with quasi-monochromatic γ-ray beams. This method is based on the fact that the particle threshold of a long-lived fission product (LLFP) such as 93 Zr, 107 Pd, or 79 Se is lower than those of stable isotopes of the same chemical element. Therefore, this method has the excellent advantage that LLFPs cannot, in principle, be produced newly even if the target materials include stable isotopes in addition to LLFPs. Furthermore, this method is effective for 126 Sn, 135, 137 Cs, 90 Sr, and 3 H. The nuclear data involved and suitable γ-ray sources are discussed. Laser Compton scattering γ-ray sources and neutron capture γ-rays in nuclear reactors are candidates for this method.